2006
DOI: 10.1038/sj.emboj.7601002
|View full text |Cite
|
Sign up to set email alerts
|

Two E3 ubiquitin ligases, SCF-Skp2 and DDB1-Cul4, target human Cdt1 for proteolysis

Abstract: Replication licensing is carefully regulated to restrict replication to once in a cell cycle. In higher eukaryotes, regulation of the licensing factor Cdt1 by proteolysis and Geminin is essential to prevent re-replication. We show here that the N-terminal 100 amino acids of human Cdt1 are recognized for proteolysis by two distinct E3 ubiquitin ligases during S-G2 phases. Six highly conserved amino acids within the 10 first amino acids of Cdt1 are essential for DDB1-Cul4-mediated proteolysis. This region is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
488
2
22

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(551 citation statements)
references
References 51 publications
(92 reference statements)
36
488
2
22
Order By: Relevance
“…DDB1 in particular is involved in many distinct DNA response and DNA repair pathways. For example, DDB1 binds to SKP2 and plays a role in the ubiquitination of CDKN1B, a cyclin-dependent kinase inhibitor (Nishitani et al 2006) and may recruit nucleotide excision repair proteins in order to repair DNA damage (Li et al 2006). Deficiency in DDB1 is associated with xeroderma pigmentosum (Kapetanaki et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…DDB1 in particular is involved in many distinct DNA response and DNA repair pathways. For example, DDB1 binds to SKP2 and plays a role in the ubiquitination of CDKN1B, a cyclin-dependent kinase inhibitor (Nishitani et al 2006) and may recruit nucleotide excision repair proteins in order to repair DNA damage (Li et al 2006). Deficiency in DDB1 is associated with xeroderma pigmentosum (Kapetanaki et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…8 Although by a still elusive mechanism, the rapid and dose-dependent degradation of c-MYC in cells after UV-irradiation that we report here is reminiscent of the UV-induced degradation of the replication licencing factor Cdt1 that requires the presence of L2DTL, PCNA and the DDB1/CUL4 E3 ligase complexes. [60][61][62] It has been shown that c-MYC overexpression antagonizes the p53-dependent cell cycle arrest following DNA damage. 63,64 Consequently, an excess of c-MYC promotes chromosomal instability probably by combined effects since it increases DNA damage and it overcomes cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type, ΔMBI (aa [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] and ΔMBII (aa 129-143) N-terminally FLAG tagged c-MYC2 coding pcDNA3 plasmids were kindly provided by Dr B. Lüscher (Institut für Biochemie, Aachen, Germany). ΔMBIII (aa 129-143), ΔA (aa 1-63), ΔB (aa 64-126), ΔC (aa 127-189), ΔD (aa 190-252), ΔE (aa 253-315), ΔF (aa 316-378), ΔG (aa 379-439), ΔCT (aa 354-439), T58A S62A and T358A S373A T400A deletions and point mutations were done by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cotransfected Geminin increased the expression of both WT and DPEST Cdt1 (Fig. 3b), indicating that by blocking origin licensing and S-phase entry Geminin indirectly inhibited DNA synthesiscoupled degradation 13 of both Cdt1 variants. Finally, coimmunoprecipitation experiments indicated that the PEST deletions did not affect the Cdt1-Geminin interaction (Fig.…”
Section: Resultsmentioning
confidence: 99%